El inductismo aritmético y su influencia en la enseñanza del número - Ortiz Comas, Alfonso; González Marí, José Luis (Aula, 2009)
RESUMEN: En este artículo presentamos las características de una corriente epistemológica y matemática que hemos denominado inductivismo aritmético. Exponemos dos hechos fundamentales para la Educación Matemática, como son la confirmación de la influencia del inductivismo en los manuales de aritmética publicados en España desde el siglo XVI y su repercusión en la enseñanza de la aritmética del número natural. Además, exponemos algunas consideraciones inductivistas sobre las series y sucesiones de números naturales. ABSTRACT: Arithmetic Inductivism is an epistemological approach to Arithmetic with specific characteristics which are analysed in the present paper. Additionally, the two following fundamental facts for Mathematics Education are also explained: Firstly, the influence of inductivism trend on arithmetical concepts as it can be appreciated by examinning the books published in Spain since the XVIth century to now; secondly, its influence on teaching and learning natural numbers and school arithmetic. Finally, some remarks about inductive reasoning related to natural numbers series are included.